Penggunaan Regresi Data Panel pada Analisis Indeks Pembangunan Manusia - Limah Olivia Alviani (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Human development index is important component to measure the success level in effort to improve the human life quality. This index has three dimensions, they are called the dimensions of health, the dimensions of education, and the dimensions of decent living standards. The health dimension is measured by using life expectancy. The education dimension is measured by using the expected length of schooling and the average length of schooling. Meanwhile, the standard of living is measured using real per capita expenditure in rupiah. This study aims to find the cause that affects the human development index, and the best model is using panel data as a regression method. The results shown that the human development index is influenced by life expectancy, long school expectations, average length of schooling and per capita expenditure. The model used in this study is named fixed effect model with a coefficient of determination of 99.99%, which means that this model is good enough to be used. Abstrak. Indeks pembangunan manusia yaitu salah satu komponen penting untuk mengukur tingkat keberhasilan dalam upaya meningkatkan kualitas hidup manusia. Indeks pembangunan manusia dibangun dengan tiga dimensi yaitu dimensi kesehatan, dimensi pendidikan serta dimensi standar layak hidup. Dimensi kesehatan diukur menggunakan angka harapan hidup. Dimensi pendidikan diukur menggunakan harapan lama sekolah dan rata-rata lama sekolah. Sedangkan dimensi standar layak hidup diukur menggunakan pengeluaran per kapita riil dalam rupiah. Penelitian ini bertujuan untuk mencari faktor yang mempengaruhi indeks pembangunan manusia dan model yang terbaik menggunakan metode regresi data panel. Hasil yang diperoleh yaitu indeks pembangunan manusia dipengaruhi oleh angka harapan hidup, harapan lama sekolah, rata-rata lama sekolah dan pengeluaran per kapita. Model yang digunakan pada penelitian ini yaitu fixed effect model dengan nilai koefisien determinasinya sebesar 99,99% yang berarti model ini baik di gunakan.